Genetic characterization of Shiga toxin-producing Escherichia coli O26:H11 strains isolated from animal, food, and clinical samples - Krüger, Alejandra; Lucchesi, Paula M. A.; Sanso, A. Mariel; Etcheverría, Analía I.; Bustamante, Ana V.; Burgán, Julia; Fernández, Luciana; Fernández, Daniel; Leotta, Gerardo; Friedrich, Alexander W.; Padola, Nora L.; Rossen, John W. A. (Frontiers in Cellular and Infection Microbiology, 2015)
The Shiga-toxin producing Escherichia coli (STEC) may cause serious illness in human. Here we analyze O26:H11 strains known to be among the most reported STEC strains causing human infections. Genetic characterization of strains isolated from animal, food, and clinical specimens in Argentina showed that most carried either stx1a or stx2a subtypes. Interestingly, stx2a-positive O26:H11 rarely isolated from cattle in other countries showed to be an important proportion of O26:H11 strains circulating in cattle and food in our region. Seventeen percent of the isolates harbored more than one gene associated with antimicrobial resistance. In addition to stx, all strains contained the virulence genes eae-β, tir, efa, iha, espB, cif, espA, espF, espJ, nleA, nleB, nleC, and iss; and all except one contained ehxA, espP and cba genes. On the other hand, toxB and espI genes were exclusively observed in stx2-positive isolates, whereas katP was only found in stx1a-positive isolates. Our results show that O26:H11 STEC strains circulating in Argentina, including those isolated from humans, cattle and meat products, present a high pathogenic potential, and evidence that cattle can be a reservoir of O26:H11 strains harboring stx2a.